New RP‐CVD grown ultra‐high performance selectively B‐doped pure‐Ge 20 nm QWs on (100)Si as basis material for post‐Si CMOS technology. Issue 1 (9th December 2013) - Mironov, O. A.; Hassan, A. H. A.; Uhlarz, M.; Kiatgamolchai, S.; Dobbie, A.; Morris, R. J. H.; Gabani, S.; Berkutov, I. B.; Leadley, D. R.; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; et al.
Abstract Magnetotransport studies at low and room temperature are presented for two‐dimensional hole gases (2DHG) formed in fully strained germanium (sGe) quantum wells (QW). Two designs of modulation doped heterostructure grown by reduced pressure chemical vapour deposition (RP‐CVD) were used and included a normal structure (doping above the Ge channel and inverted structure (doping beneath the Ge channel). The mobility (μH) for the normal structure was measured to be 1.34×106 cm2/Vs with a sheet density (ps) of 2.9×1011cm‐2at 1.5 K, and μH= 3970 cm2/Vs and ps ∼1×1011cm‐2 for room temperature, determined from simulation using the Maximum Entropy‐Mobility Spectrum Analysis (ME‐MSA) method. For the inverted structure a μH of 4.96×105 cm2/Vs and ps of 5.25×1011cm‐2was measured at 90 mK. From the temperature dependent amplitude of Shubnikov de Haas oscillations, the normal structure was found to have a very low effective mass (m*) value of 0.063 m0 and a ratio of transport to quantum lifetime (α) of ∼78. This extremely high α is indicative of the carrier transport being dominated by small angle scattering from remote impurities i.e. a sample having an extremely low background impurity level and very smooth hetero‐interfaces. The inverted structure had an m*of 0.069 m0 and α ∼29, which also indicates exceedingly high quality material. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)